El proceso contable de la junta administradora de agua potable de la comunidad San José de Gaushi parroquia Calpi cantón Riobamba y su incidencia en el manejo de los recursos en el año 2015 - Hiza Hiza, Clara Yadira (2018)
The Administrative Board of the San José de Gaushi Community is summarized through the accounting process, which takes the data from the receipt and deposit receipts to register and process them, The main objective of the research was to analyze the accounting process and the impact on the management of economic resources in 2015 to raise awareness, since this summary information is presented before the general assembly of the partners. The methodology was based on the deductive method, because the general information of the accounting process and the movement of income and expenses were taken. So this research is descriptive because the objective was to get to describe the accounting process and how economic resources were managed, and with a non-experimental research design so that the accounting information was observed and taken without that the investigation manipulates them for any circumstance, documentary and field, the techniques used were of observation and interview to the treasurer and president of the Administrative Board. The results obtained show that the accounting process is deficient on the part of the accountant reviewing the documentation corresponding to the year 2015, since in the information delivered by the treasurer It throws a good management of the resources but in the statements of results there is requested reason why it is advisable to return to restructure in a correct way the whole accounting process so that it is reliable for the assembly of the partners and know with how much of money they have for a correct decision making.